Divergência genética entre progênies de Pinus caribaea var. caribaea com base em caracteres quantitativos - Silva, Janete Motta da [UNESP] (2012)
The objective of this research was to quantify the genetic dissimilarity among. P. caribaea var. caribaea progenies to identify divergent parents aiming to generate highly productive genotypes and to evaluate the total variability by phenotypic characters of commercial importance. The progeny trial of P. caribaea var. caribaea was set up through 10 x 10 triple lattice design, with 99 progenies and a commercial control in Selvíria, MS, Brazil. We have evaluated quantitative characters before and after thinning procedures such as: total plant height (m), diameter at breast height (dbh) (cm); wood volume (m3 tree-1), stem form, wood density at dbh and wood density at the middle of the total height of tree stem (g cm-3), and survival of progenies (%). There was low genetic divergence among P. caribaea var. caribaea progenies. The diameter at breast height was the character that most contributes to genetic diversity among progenies, for both before and after thinning. The information of Mahalanobis distance and the clustering of progenies by Tocher's method will be important to define the future strategies for breeding programs and genetic conservation of the species.